The Institutional Ingredients of Polycrisis Management: Unpacking European Council’s Handling of the Energy Crisis - Smeets, Sandrino (2023)
This article analyses how the European Council and the institutional infrastructure that supports it have been managing the early stages of the energy crisis. This was the time when the European Council, as the “control room” of EU crisis management, was unable to come up with any solutions to high energy prices. It makes a methodological and empirical contribution to the debate on how the European Council system manages (poly)crises. Methodologically, we introduce the method of embedded process tracing to study EU crisis management from within. Embedded process tracing combines mainstream causal process tracing techniques with elements from interpretivist approaches, to deal with context dependency, case heterogeneity, and empirical density. Empirically, we offer a process-management analysis of the first nine months of the energy crisis. We delineate the roles of various actors and institutions: the president of the European Council, the Council Secretariat, the Commission president, and the Commission Services. We unpack the crucial ingredients of polycrisis management: how to get and keep an issue on the agenda, how to shape and steer European-Council-level debates and conclusions, and how to ensure a proper follow-up by the Commission and the Council. Finally, we re-assess the image of the malfunctioning control room and show the causal relevance of the European Council’s early performance.